Palladium‐Based Dyotropic Rearrangement Enables A Triple Functionalization of Gem‐Disubstituted Alkenes: An Unusual Fluorolactonization Reaction - Feng, Qiang; Liu, Chen‐Xu; Wang, Qian; Zhu, Jieping (Angewandte Chemie International Edition, 2024)
We report in this paper a Pd(II)‐catalyzed migratory gem‐fluorolactonization of ene‐carboxylic acids. Reaction of 4‐methylenealkanoic acid derivatives with Selectfluor in the presence of Pd(OAc)2 (1.0 mol %) at room temperature affords fluorolactones in good to excellent yields. 2‐(2‐Methylenecycloalkanyl)acetic acids are transformed to bridged fluorolactones under identical conditions. One C−C, one C−O and one tertiary C−F bond were generated along the gem‐disubstituted carbon‐carbon double bond in this operationally simple transformation. Trapping experiments indicates that the reaction is initiated by a 5‐exo‐trig oxypalladation followed by Pd oxidation, regioselective ring‐enlarging 1,2‐alkyl/Pd(IV) dyotropic rearrangement and C−F bond forming reductive elimination cascade. Post‐transformations of these fluorolactones taking advantage of the electrophilicity of the 1‐fluoroalkylcarboxylate function are also documented. Pd‐catalyzed reaction of 4‐methylenealkanoic acid derivatives with Selectfluor provides fluorolactones via a sequence of 5‐exo‐trig oxypalladation, Pd oxidation, regioselective ring‐enlarging 1,2‐alkyl/Pd(IV) dyotropic rearrangement and C−F bond‐forming reductive elimination.